2017
DOI: 10.1112/jlms.12038
|View full text |Cite
|
Sign up to set email alerts
|

p-Selmer growth in extensions of degree p

Abstract: Abstract. There is a known analogy between growth questions for class groups and for Selmer groups. If p is a prime, then the p-torsion of the ideal class group grows unboundedly in Z{pZ-extensions of a fixed number field K, so one expects the same for the p-Selmer group of a nonzero abelian variety over K. This Selmer group analogue is known in special cases and we prove it in general, along with a version for arbitrary global fields.1. Introduction 1.1. Growth of class groups and of Selmer groups. It is a cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The fppf cohomology was used in the original statement of [Čes17, Theorem 4.2]. Here we rephrase it in the language of Galois cohomology, due to the canonical isomorphism (see [Čes15b, p. 1661, equation (1)]), where , is the Néron model of and with the proper smooth curve over a finite field whose function field is .…”
Section: Growth Of -Selmer Ranks In Degree Cyclic Extensionsmentioning
confidence: 99%
See 3 more Smart Citations
“…The fppf cohomology was used in the original statement of [Čes17, Theorem 4.2]. Here we rephrase it in the language of Galois cohomology, due to the canonical isomorphism (see [Čes15b, p. 1661, equation (1)]), where , is the Néron model of and with the proper smooth curve over a finite field whose function field is .…”
Section: Growth Of -Selmer Ranks In Degree Cyclic Extensionsmentioning
confidence: 99%
“…Theorem 1.1 [Čes17,Theorem 1.2]. Let p be a prime number, and A be an abelian variety over a global field K. If either A[p]( K) = 0 or A is supersingular, then dim Fp Sel p (A/L) is unbounded as L varies over (Z/pZ)-extensions of K.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [Čes17], Česnavičius showed that the p -Selmer group of elliptic curves over a number field becomes arbitrarily large when varying over -extensions. This result is not surprising, as it is widely believed that the growth of ideal class groups and Selmer groups of elliptic curves are often analogous.…”
Section: Introductionmentioning
confidence: 99%